2016
DOI: 10.1177/1367006915576398
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of English number agreement: L1 Cantonese–L2 English–L3 French speakers versus L1 Cantonese–L2 English speakers

Abstract: Purpose: Drawing on the notions of ‘interface’ and ‘cross-linguistic influence’ in second language acquisition (L2A), the present study addresses the possible role of French as a third language (L3) in the L2A of English number agreement with two major concerns: (1) the degree to which third language acquisition (L3A) will bring about any positive or negative influence on L2A, and (2) the way in which an L3 interacts with L2 and/or even L1 on narrow syntax or an internal interface as identified in L2A. Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Moreover, further studies could benefit from discriminating between subjects according to their dominant L1 language, since in line with previous studies (Tsang, 2016;Luque-Agulló, 2020), transfer may happen with greater knowledge of L3 or L2.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, further studies could benefit from discriminating between subjects according to their dominant L1 language, since in line with previous studies (Tsang, 2016;Luque-Agulló, 2020), transfer may happen with greater knowledge of L3 or L2.…”
Section: Resultssupporting
confidence: 52%
“…The study by Brown and Gullberg (2008) examined the transfer between Japanese (L1) and English (L2) in the expression of motion and found that there was a difference between monolingual speakers of Japanese as opposed to bilingual speakers, since the latter made a shift towards the English rhetorical style in the expression of motion. Finally, a last study (Tsang, 2016) analysed the use of plural markers in combination with quantity markers by Chinese (Cantonese) speakers (L1) with English as their L2 and who were learning French as an L3. The conclusion was that there was a certain transfer from L3 to L2 especially in subjects with higher proficiency in L3.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies examine whether the L3 can have a cumulative enhancement effect on L2 acquisition. These are the studies where the property under investigation behave similarly in the L3 and L2, thus, speeding up the acquisition process (Cheung et al, 2011; Hui, 2010; Llinàs-Grau & Puig-Mayenco, 2016; Tsang, 2016). These studies do not allow us to draw conclusions for our data because (a) they did not prove for negative regressive transfer and (b) the L1 and the L3 do not share the same distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In line with Hui’s study, the results show a positive/cumulative effect from L3 German to L2 English. In another study, Tsang (2016) compared speakers of L1-Cantonese, L2-English with and without L3 French on the knowledge of number marking in the nominal domain in two different tasks: a grammaticality judgement task and a production one. His results show an effect of L3 French on L2 English on the production task only, suggesting that L3 influence plays a more important role at the production level; recall this is what Cabrelli Amaro (2017) found for phonology.…”
Section: Studies On Regressive Transfermentioning
confidence: 99%
“…He argues that the backward transfer from L3 German to L2 English can probably be driven by a closer language distance between these two languages, as well as high frequency of language use and language exposure [6]. In another research on the English number agreement among L3 learners, Tsang (2015) used a grammaticality judgment-correction task and a free writing task and found that there was a possible reverse transfer from L3 French to L2 English among the Cantonese-English-French participants [7]. He proposes that the transfer effect from L3 French to L2 English can only take place when a learner's L3 proficiency has reached a certain threshold [8].…”
Section: Literature Reviewmentioning
confidence: 99%